2006
DOI: 10.1111/j.0105-2896.2006.00395.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional signatures of protective antiviral T‐cell immunity in human virus infections

Abstract: The most common human viruses have different abilities to establish persistent chronic infection. Virus-specific T-cell responses are critical in the control of virus replication and in the prevention of disease in chronic infection. A large number of phenotypic markers and a series of functions have been used to characterize virus-specific CD4+ and CD8+ T-cell responses, and these studies have shown great phenotypic and functional heterogeneity of the T-cell responses against different viruses. The heterogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
232
0
9

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 242 publications
(260 citation statements)
references
References 149 publications
(380 reference statements)
19
232
0
9
Order By: Relevance
“…Such acute infections trigger the generation of large numbers of short-lived effector T-cells and the formation of memory T-cells [1][2][3][4][5][6][7][8] . Following such infections, T-cells typically co-express multiple cytokines (TNF, IFN IL-2) and cytotoxic effector molecules -a phenotype often referred to as polyfunctional 9 . A different outcome arises when infections become chronic and when viruses persist at high levels over long periods as in Human-Immunodeficiency-Virus (HIV) or Human-Hepatitis-C Virus (HCV) infections.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such acute infections trigger the generation of large numbers of short-lived effector T-cells and the formation of memory T-cells [1][2][3][4][5][6][7][8] . Following such infections, T-cells typically co-express multiple cytokines (TNF, IFN IL-2) and cytotoxic effector molecules -a phenotype often referred to as polyfunctional 9 . A different outcome arises when infections become chronic and when viruses persist at high levels over long periods as in Human-Immunodeficiency-Virus (HIV) or Human-Hepatitis-C Virus (HCV) infections.…”
Section: Introductionmentioning
confidence: 99%
“…A different outcome arises when infections become chronic and when viruses persist at high levels over long periods as in Human-Immunodeficiency-Virus (HIV) or Human-Hepatitis-C Virus (HCV) infections. Such conditions induce T-cells lacking the typical polyfunctional phenotype and T-cells retain the expression of inhibitory receptors including PD-1, Lag-3, Tim-3, and CD160 [9][10][11][12][13][14][15][16][17] . Very similar phenotypes can be observed, when T-cells are long-term exposed to tumor-antigen [18][19][20] .…”
Section: Introductionmentioning
confidence: 99%
“…Studies of chronic viral infections such as cytomegalovirus, Epstein-Barr Virus, and others have highlighted the phenotypic and functional heterogeneity of the antigenspecific CD4 1 and CD8 1 T-cell responses, and provided evidence that they are dependent on, and modulated by, antigen concentration [6]. Overall it has been shown that polyfunctional T cells that secrete multiple cytokines and are able to proliferate are more likely than single cytokine secretors to represent correlates of protective antiviral immunity in chronic infections (when antigen load is low), while single IFN-g-secreting CD4 1 and CD8 1 T cells are characteristic of acute infections (when antigen load is high) [7]. If chronic infection ensues after failure of complete immune control, the balance of responding T cells tends to shift towards the single IFN-g-secreting phenotype.…”
mentioning
confidence: 99%
“…Central memory T-cells have high proliferative activity and produce IL-2, whereas effector memory T-cells produce bothIL-2 and IFN-γ. Circulating effector memory T-cells indicates that an antigen-specific response persists, whereas circulating central memory T-cells indicate that infection has been controlled [28]. …”
Section: Only Sometimes Immunity Holds On Tightlymentioning
confidence: 99%